MicroRNA expression profile analysis of skin immune response in crucian carp (Carassius auratus) infected by Aeromonas hydrophila. Issue 104 (September 2020) - Bai, Jie; Hu, Xiucai; Wang, Ruixia; Lü, Aijun; Sun, Jingfeng
Abstract: MicroRNAs (miRNAs) are non-coding RNA molecules that regulate gene expression in fish, but its regulatory mechanism of the skin mucosal immune response remains poorly understood. In order to investigate the immunological role of miRNAs, three sRNA libraries (mSC, mST1, mST2) from skin samples of crucian carp ( Carassius auratus ) infected with Aeromonas hydrophila at three time points (0, 6 and 12 hpi) were constructed and examined using Illumina Hiseq 2000 platform. All of the identified miRNA, rRNA and tRNA were 69444 (13.39%), 29550 (5.70%) and 10704 (2.06%) in skin, respectively. At 6 and 12 hpi, 829 and 856 miRNAs were differentially expressed, respectively. Among these DEMs, 53 known and 10 novel miRNAs were all significantly differentially expressed during early infection ( p < 0.01). GO and KEGG enrichment analyses revealed that 118111 target-genes were primarily involved in cellular process, metabolic process, biological regulation and stress response, such as antigen processing and presentation, complement and coagulation cascades, phagosome, MAPK, TLR, NF-κB and JAK-STAT signaling pathways. These results will help to elucidate the mechanism of miRNAs involved in the skin mucosal immune response of crucian carp against Aeromonas hydrophila infection. Highlights: This was first report on skin miRNAs profiles of C. auratus upon A. hydrophila infection. 829 and 856 DEMs in skin were identified at 6 and 12 hpi, respectively. 10 novel miRNAs were significantly differentially expressed during early infection. Antigen presentation, complement, MAPK, TLR and NF-κB pathways were significantly involved in skin mucosal immunity.